THE INFLUENCE OF HUMAN RESOURCE QUALITY AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CV. BUMI ADIL IN KEC.TEGINENENG KAB.PESAWARAN - Yusneli, Erma; Parela, Epi (University of Sang Bumi Ruwa Jurai, 2024)
Human Resources (HR) has a very important role as the potential for all company activities. The success of an organization or organization is influenced by employee performance or the work achieved by an employee in performing tasks in accordance with the responsibilities given to him. Human resources have a very strategic position in the organization, which means that the human element plays an important role in carrying out activities to achieve goals. The better the quality of human resources in a company, the higher the competitiveness of the company against other companies. The human resource management system is very important for the effectiveness of running activities or sustainability in a company. Good and maximum HR management will provide maximum employee performance output. Another factor that is believed to contribute to high and low performance is compensation for employees. Employees will tend to show their best performance if the organization pays proper attention and meets the needs of employees. The purpose of this research is to find out: 1. The effect of infrastructure facilities on employee performance 2. The effect of compensation on employee performance 3. The effect of infrastructure facilities and compensation together on the performance of UPTD employees of the PSDA Service Region I Pringsewu. This research uses descriptive quantitative research methods, namely research methods that use data in the form of numbers in analyzing the facts found which aim to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This study used 47 respondents. Based on the results of data analysis, the answers to the hypotheses are found, namely as follows; There is an influence of Infrastructure Facilities (X1) on Performance (Y) at UPTD Dinas PSDA Region I Pringsewu, with an influence level (R-square) of 69.8%. There is an influence of Compensation on Performance at UPTD Dinas PSDA Wilayah I Pringsewu with an influence level of 88%. There is an influence of Infrastructure Facilities and Compensation together on Performance at UPTD Dinas PSDA Wilayah I Pringsewu, with an influence level of 89.2%.